Aligning religious law and state law: negotiating legal Muslim marriage in Pasuruan, East Java - Fauzi, Muhammad Latif (Leiden studies in Islam and society, 2023)
"In Aligning Religious Law and State Law: Negotiating Legal Muslim Marriage in Pasuruan, East Java, Muhammad Latif Fauzi investigates the extent to which the Indonesian state has regulated Muslim marriage and how a local community in Pasuruan, East Java has dealt with the regulation and gets their marriages recognised by the state. Instead of reforming the marriage law which would only stir up controversies, the Indonesian government has used a citizens' rights approach to control marriage to guide people towards compliance with the state legal framework. The state officials in charge of marriage registration on the frontier levels are amenable to adopting a lenient approach towards regulations on marriage, which is the key to securing the functioning of state law"--